Proceedings of the 58th Annual Meeting of the Association for Computational Linguistics 2020
DOI: 10.18653/v1/2020.acl-main.369
|View full text |Cite
|
Sign up to set email alerts
|

CluBERT: A Cluster-Based Approach for Learning Sense Distributions in Multiple Languages

Abstract: Knowing the Most Frequent Sense (MFS) of a word has been proved to help Word Sense Disambiguation (WSD) models significantly. However, the scarcity of sense-annotated data makes it difficult to induce a reliable and highcoverage distribution of the meanings in a language vocabulary. To address this issue, in this paper we present CluBERT, an automatic and multilingual approach for inducing the distributions of word senses from a corpus of raw sentences. Our experiments show that Clu-BERT learns distributions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…This architecture was originally proposed for machine translation following the sequence‐to‐sequence paradigm. Later works successfully applied Transformer‐based models to various Natural Language Processing tasks [ZHLL20, PSS20], typically adopting the pretrain‐then‐fine‐tune paradigm [DCLT19]. Its flexibility has been then proven with success also in other domains, such as Computer Vision [DBK*21], Computer Graphics [LYZ22], Speech Processing [WML*20], Reinforcement Learning [CLR*21], and on mixed modalities, such as Vision and Language [KSK21].…”
Section: Related Workmentioning
confidence: 99%
“…This architecture was originally proposed for machine translation following the sequence‐to‐sequence paradigm. Later works successfully applied Transformer‐based models to various Natural Language Processing tasks [ZHLL20, PSS20], typically adopting the pretrain‐then‐fine‐tune paradigm [DCLT19]. Its flexibility has been then proven with success also in other domains, such as Computer Vision [DBK*21], Computer Graphics [LYZ22], Speech Processing [WML*20], Reinforcement Learning [CLR*21], and on mixed modalities, such as Vision and Language [KSK21].…”
Section: Related Workmentioning
confidence: 99%
“…However, their main drawback is that they have difficulty scaling over different languages, since no manually-curated training data is available to them. Automatic methods to produce sense distributions (Pasini, Scozzafava, and Scarlini 2020) or sense-annotated data in languages other than English (Delli Bovi et al 2017;Scarlini, Pasini, and Navigli 2019;Pasini and Navigli 2020; Pasini 1 http://wordnetcode.princeton.edu/glosstag.shtml 2020) have mitigated this limitation, thus allowing supervised approaches to be trained on different languages and to enter a field that was mainly dominated by knowledge-based methods.…”
Section: Related Workmentioning
confidence: 99%
“…Hadiwinoto et al (2019); Coenen et al (2019) showed that this technique works well with BERT too. Pasini et al (2020) uses a combination of BERT embeddings and a knowledge-based WSD model to generate word sense distributions, while Giulianelli et al (2020) uses clustering over the embeddings to detect semantic shifts.…”
Section: Related Workmentioning
confidence: 99%